Introductory analysis of the report of The Truth and Reconciliation Commission of Norway - Hlebowicz, Sylwia (Studia Scandinavica, 2024)
In June 2023 the Truth and Reconciliation Commission of Norway submitted its reportto the Norwegian parliament. Norway is the first Scandinavian country to appoint such a consultativebody. The Commission had three objectives: to outline Norwegian assimilation policies,examine the present-day repercussions of the assimilation policy towards Sami and Kven/ Finnishpeople, and contribute to further reconciliation. The present paper presents an abridged analysisof the Commission’s report set against historical and legislative backdrops. Such an approachbroadens the interpretative perspective of the report and places the Commission’s conclusionsin the appropriate socio-cultural context.